Pengaruh Flipped Classroom Model Berbantuan Video Interaktif Terhadap Pemahaman Konsep IPS Siswa Kelas V di SD Wujud Kasih Ungaran - Kristina Cahyo Saputro; Kartika Yuni Purwanti (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This study aims to investigate the effect of using the Flipped Classroom model assisted by interactive videos on the understanding of social science concepts among fifth-grade students at SD Wujud Kasih Ungaran. The research method employed is quantitative, with the subjects being fifth-grade students. Through an experimental design, this research compares two groups: an experimental group utilizing the Flipped Classroom model and a control group employing conventional methods. The results indicate that the implementation of the Flipped Classroom model assisted by interactive videos has a positive impact on students' understanding of social science concepts. Data analysis using the Independent Sample T-Test reveals a significance value of 0.023, indicating a significant difference between the experimental and control groups at a significance level of 0.05. The average understanding score of the experimental group reached 61.61 percent, higher than that of the control group. Furthermore, the results of the Simple Linear Regression Test show an R square value of 0.547, indicating that 54.7% of the variation in students' understanding can be explained by the use of this learning model. In conclusion, the Flipped Classroom model assisted by interactive videos significantly influences students' understanding of social science concepts, as evidenced by increased enthusiasm and motivation during the learning process. This study recommends the adoption of this model as an alternative in social science education to enhance students' understanding quality.